Isen????es e anterioridade tribut??ria: quest??es controvertidas quanto a sua revoga????o - Dias, Murilo Boscoli (2017)
The purpose of this paper is to study the tax, the discharge policies by the exemptions and legal security , passing by the study of fiscal benefits and in its stimulation function, na its aspects among the history. The paper of the tax was modifying over the eyers, where its leave to be a fiscal instrument and become a stimulation instrument by the implement of public and economic policies, gaining prominence the fiscal benefits that can be identified by more than one way, but mainly by the figure of exemption, which is gaining more importance, includ with more budget regulations. The exemptions by another way means a performance by the public entity, who leaves facts in Its constitutional competence from tributation, by option, to promove some goals. In this point exemptions are importants economic and social instruments, and cant be seen by only favors to the taxpayer, but It stimulate the taxpayer to take decisions, where the revocation of the exemptions have to be analyzed by the view of legal security, and the tax anteriority.